Universities and Sustainable Development: Options to Help ‘Walk the Talk’ - Supaat, Khadijah; Aziz, Sarah; Hasan, Siti Zuhaili; Basri, Noor Ezlin Ahmad; Shafie, Siti Haslina Mohd (Journal of Ecohumanism, 2024)
The United Nations’ agenda on sustainable development, since 1972 via the Stockholm Declaration 1972, the 1992 Rio Agenda 21, and the 2030 Agenda for Sustainable Development, has consistently earmarked academia as an agent of change. Academia, i.e., institutions of higher education are seen as major contributors to help governments contribute to national aspirations for sustainable development, which in turn contributes to global aspirations. Since the adoption of the SDG 2030, universities have begun to incorporate SDGs into their institutional systems and processes. This paper will briefly review related literature pertaining to the role of universities in mainstreaming sustainable development, to help determine the shift needed for universities in Malaysia to embed sustainable development into its governance systems and processes. A list of what is expected of universities, and how such expectations can be accommodated will facilitate determination of key areas to drive change. It will also explore the role of universities as a ‘living lab; medium for influence; connector with civil society; and contributors to the knowledge, and know-how related to sustainable development. Options for consideration related to embedding the sustainable development agenda within the governance framework will be highlighted in the paper.